The Saga of the Management of Fisheries in the Adriatic Sea: History, Flaws, Difficulties, and Successes toward the Application of the Common Fisheries Policy in the Mediterranean - Carpi, Piera; Scarcella, Giuseppe; Cardinale, Massimiliano (Frontiers in Marine Science, 2017)
In the past 40 years, the fishery in the Mediterranean Sea has seen numerous changes in technology, fleet composition, effort allocation and management strategies. In this paper, our aim is to summarize the improvements, and highlight the flaws and difficulties that have characterised fisheries management in the Mediterranean Sea in the past decades. We (the authors) advocate the importance of the regionalisation of the Common Fisheries Policy (CFP) in the Mediterranean. We focused on the Adriatic Sea, with two case studies - the fishery for sardine and anchovy, and the fishery for Nephrops. The former is emblematic as it is one of the most valuable and well-studied fisheries in the Mediterranean but it is also an example of a management process that is slowly bearing fruit. Nephrops, on the other hand, has been facing the same destiny as other stocks in the Mediterranean; namely, its peculiar biology, a complex fishery, a poorly tailored data collection and inadequate assessments, have delayed action until very recent times. We use these examples to cover several aspects of Mediterranean fisheries management: i) a historical overview of the development of these fisheries and their management; ii) an overview of the main players involved in the scientific analysis and management process and their current and ideal roles; iii) the flaws of the current stock assessment system; and iv) recent developments and potential solutions to comply with the latest reform of the CFP before 2020. We argue that to align Mediterranean management with the CFP and achieve MSY targets, the lack of coordination and definition of roles between the General Fisheries Commission for the Mediterranean, the European Commission Directorate-General for Maritime Affairs and Fisheries, the Scientific, Technical and Economic Committee for Fisheries and the Joint Research Centre need to be resolved. There is a need for adequate assessment models and data to answer increasingly complex management questions, as well as regular external review of the stock assessment models to assure their quality. Finally, the need for the implementation of a TAC management system as an effective tool for Mediterranean fisheries to achieve sustainability is discussed and advocated.